1995
DOI: 10.1002/etc.5620140302
|View full text |Cite
|
Sign up to set email alerts
|

Submitochondrial particles as toxicity biosensors of chlorophenols

Abstract: An in vitro bioassay procedure was used to investigate the toxic action of chlorophenols on mitochondrial respiratory parameters The toxicity of these compounds was evaluated by determining their effects on the energy coupled reverse electron transfer (RET) in submitochondrial particles (SMPs) from beef heart mitochondria The bioassay procedure is based on the spectrophotometric recording of the effects of toxicants on the rate of NAD+ reduction, induced by ATP and succinate at the first site level of the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Chlorophenols are pollutants that originate from pulp bleaching effluents, pesticide manufacturing, wood-preserving agents, and combustion ashes. They uncouple oxidative phosphorylation [4][5][6], thus disrupting the regulation of energy metabolism. The sublethal bioenergetic response caused by these toxicants can be detected at organism level by monitoring their rate of energy metabolism, e.g., heat dissipation, and the response should reflect the increased metabolic rate of the animal [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophenols are pollutants that originate from pulp bleaching effluents, pesticide manufacturing, wood-preserving agents, and combustion ashes. They uncouple oxidative phosphorylation [4][5][6], thus disrupting the regulation of energy metabolism. The sublethal bioenergetic response caused by these toxicants can be detected at organism level by monitoring their rate of energy metabolism, e.g., heat dissipation, and the response should reflect the increased metabolic rate of the animal [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The authors also reported a mean EC for zinc (as ZnSO ) in the RET assay of 1700$110 ppb (n"2; CV"6.5%) compared with a composite EC of 2100$190 g/L and a CV of 9.1% (as Zn) in this study. Argese et al (1995) assessed the reproducibility and stability of the SMP response during a 12-h working period by conducting eight tests with a stock solution of an unidenti"ed toxicant and the same SMP stock suspension. The authors reported that the response reproducibility of the SMP test was within a relative 95% CI of 7%, as calculated by applying the Student distribution to the EC values obtained by eight replicates.…”
Section: Discussionmentioning
confidence: 99%
“…The use of SMP as a surrogate in water quality assessments and aquatic toxicity testing has been promoted by its developers (Blondin et al, 1987(Blondin et al, , 1989Knobeloch et al, 1990b) and supported more recently by groups of Italian researchers (Argese et al, 1994(Argese et al, , 1995(Argese et al, , 1998Miana et al, 1993;and Bragadin and Dell'Antone, 1994, among others). The focus of these studies has typically been related to an assessment of the comparative sensitivity of an SMP assay with other species and tests.…”
Section: Introductionmentioning
confidence: 98%
“…The mitochondrial fraction is a good model for the study of cell toxicity of xenobiotics in energy metabolism, since data from mitochondrial studies are reasonably correlated with cytotoxicity parameters reported for cell cultures and whole organisms [1][2][3]. These organelles provide the eukaryotic cell of nonphotosynthetic tissue with more than 90% of its total energy requirements.…”
Section: Introductionmentioning
confidence: 96%